Analysis of the Needs for Developing an Integrated Sound Wave E-Module with Ethnoscience and Meaningful Learning to Facilitate Students' Knowledge and Creative Thinking Skills - Aprilia, Rani; Asrizal, Asrizal (Department of Physics Universitas Negeri Padang, 2025)
Education in the 21st century requires students to have the ability to adapt, think critically, and creatively, which is in line with the direction of the Merdeka Curriculum which emphasizes mastery of essential competencies and the formation of the Pancasila Student Profile. However, preliminary findings at SMAN 1 Lembah Gumanti indicate that there are still various obstacles in the physics learning process, especially on sound waves. These obstacles include the low use of technology-based teaching materials such as e-modules, not optimal application of ethnoscience and meaningful learning approaches, and the lack of creative thinking skills and conceptual understanding of students. Through a descriptive statistical approach, this study maps the factual conditions of learning in the school. The results of the analysis showed that the teaching materials used were still dominated by printed versions that were less attractive and did not support the development of 21st century skills. The average score of students' knowledge reached 64.9%, while creative thinking skills were still relatively low with an average score of 50.8%. On the other hand, teachers have not fully integrated local cultural values through the ethnoscience approach or optimally applied the meaningful learning approach in the learning process. These facts emphasize the need for learning innovation through the development of physics e-modules integrated with ethnoscience and meaningful learning approaches to improve learning quality.